Avian nematode parasites of some wild birds of Bangladesh - Islam, Md Rabiul; Bhuiyan, Md Aminul Islam; Begum , Aleya; Jhinu, Zannatun Nahar (Bangladesh Journal of Zoology, 2024)
The current investigation into endoparasitic helminths in wild birds from various regions of Bangladesh sheds light on a previously unexplored aspect of avian parasitology in the country. The study used specimens provided by the Padma Bridge Museum Project, a sub-project of the Bangladesh government-owned Padma Multi-purpose Bridge Project (PMBP), where dead birds were utilized for museum specimens and taxidermy. A total of 22 specimens from 21 species of wild birds were examined in this study. The samples were primarily derived from the alimentary canal (gut) and liver of the hosts. It is important to note that the study faced limitations in calculating parameters such as prevalence and intensity since all hosts were single-sampled, except in the case of the Little Cormorant, where two samples were collected, both of which were found to be infected. The study identified six cases of helminth parasite infestation in the examined bird specimens. These findings provided valuable insights into the diversity of parasites affecting these avian hosts. The specific parasite species observed, along with the host species, are as follows- Peregrine Falcon (Falco peregrinus Tunstall 1771) was infected with Serratospiculum tendo (Nitzsch 1819) in the air sacs. Grey Heron (Ardea cinerea Linnaeus 1758) showed infestation with Porrocaecumardeae (Frölich 1802) in the intestine. Little Cormorant (Microcarboniger Vieillot 1817) had two parasites found: Contracaecumrudolphii (Rudolphi 1809) in the crop and Ascaridia sp. (Dujardin 1945) in the intestine. Little Egret (Egrettagarzetta Linnaeus 1766) had Heterakis sp. (Schrank 1790) identified in the intestine. Bank Myna (Acridotheres ginginianus Latham 1790) was found to host Capillariaannulata (Milon 1800) in the crop. One notable aspect of this study is that all the parasite-host associations observed were reported as the first records in their respective hosts within Bangladesh. This finding highlights the importance of this research in enhancing our understanding of avian parasitology in the region and the potential impact of these parasites on wild bird populations. Bangladesh J. Zool. 52(1): 39-55, 2024